2021
DOI: 10.1177/00034894211047463
|View full text |Cite
|
Sign up to set email alerts
|

Orocutaneous Fistula After Oral Cavity Resection and Reconstruction: Systematic Review and Meta-Analysis

Abstract: Objective: Orocutaneous fistula (OCF) after reconstruction for oral cavity resection can lead to prolonged hospitalization and adjuvant treatment delay. Few studies have examined factors leading to OCF after oral cavity resection. Primary objective: evaluate overall incidence and factors associated with OCF after oral cavity reconstruction. Data Sources: Scopus 1960—database was searched for terms: “orocutaneous fistula,” “oro cutaneous fistula,” “oral cutaneous fistula,” “orocervical fistula,” “oral cavity sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…It could be noted that current OCF formulation rate is a little higher than that (7.7%) reported by Tassone et al. ( 27 ) who also enrolled patients with previous irradiation, there are at least three aspects contributing to the difference, first, all patients in current study received a lip split, second, the two studies have different inclusion criteria, third, previously radiated patients may not have had extensive neck surgery at the time of their salvage resections.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…It could be noted that current OCF formulation rate is a little higher than that (7.7%) reported by Tassone et al. ( 27 ) who also enrolled patients with previous irradiation, there are at least three aspects contributing to the difference, first, all patients in current study received a lip split, second, the two studies have different inclusion criteria, third, previously radiated patients may not have had extensive neck surgery at the time of their salvage resections.…”
Section: Discussionmentioning
confidence: 66%
“…On one hand, indication for bilateral neck dissection midline across the primary tumor or pathologically proven lymph nodes in the contralateral neck is related to an advanced stage disease, requiring extensive soft or bone tissue resection; increased surgery duration and intraoperative bleeding are expected. On the other hand, tissue fibrosis easily results from previous chemoradiotherapy and conversely causes poor wound healing ( 27 ). These aspects might help to predict the likelihood of OCF development in patients with the two features.…”
Section: Discussionmentioning
confidence: 99%
“…Fistulas or salivary leaks complicate postoperative management and have been reported in up to 30% of oral cavity resections requiring free flap reconstruction . A meta-analysis by Tassone et al reported a pooled prevalence of fistula in 8.6% of oral cavity resections reconstructed with free tissue. Several series have compared rates of complications between OCRFFFs and FFFs, and generally no difference has been seen; however, complication rates may have been somewhat affected by studies that were inadequately powered to detect differences on the magnitude of 5% to 10% .…”
Section: Discussionmentioning
confidence: 99%
“…A difference in the study design might have contributed to this variation. Previous chemoradiotherapy significantly posed an apparent effect on wound healing and tissue fibrosis ( 25 ). This dysfunction could explain the tendency of OCF formation in patients with previous chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 99%